2010
DOI: 10.1242/jeb.041426
|View full text |Cite
|
Sign up to set email alerts
|

The spatial frequency tuning of optic-flow-dependent behaviors in the bumblebee Bombus impatiens

Abstract: SUMMARYInsects use visual estimates of flight speed for a variety of behaviors, including visual navigation, odometry, grazing landings and flight speed control, but the neuronal mechanisms underlying speed detection remain unknown. Although many models and theories have been proposed for how the brain extracts the angular speed of the retinal image, termed optic flow, we lack the detailed electrophysiological and behavioral data necessary to conclusively support any one model. One key property by which differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
73
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 42 publications
16
73
1
Order By: Relevance
“…This is consistent with the findings of similar experiments performed on bumblebees (Baird et al, 2011;Dyhr and Higgins, 2010) and honeybees (Kirchner and Srinivasan, 1989;Srinivasan et al, 1996Srinivasan et al, , 1991. In addition, we found that bumblebees fly significantly faster when the translational optic flow is asymmetric than when the optic flow cues are strong in both eyes (checks on both walls, S checks ).…”
Section: Discussion Bumblebees Respond To Low Magnitudes Of Translatisupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the findings of similar experiments performed on bumblebees (Baird et al, 2011;Dyhr and Higgins, 2010) and honeybees (Kirchner and Srinivasan, 1989;Srinivasan et al, 1996Srinivasan et al, , 1991. In addition, we found that bumblebees fly significantly faster when the translational optic flow is asymmetric than when the optic flow cues are strong in both eyes (checks on both walls, S checks ).…”
Section: Discussion Bumblebees Respond To Low Magnitudes Of Translatisupporting
confidence: 93%
“…When flying through narrow spaces, honeybees and bumblebees use translational optic flow to control their position so as to maintain an equal distance to the nearby surfaces -a behaviour known as centring. It has been proposed that this centring behaviour is achieved by balancing the magnitude of the lateral optic flow experienced in each eye (Dyhr and Higgins, 2010;Kirchner and Srinivasan, 1989;Srinivasan et al, 1991Srinivasan et al, , 1996 or by maintaining the magnitude of unilateral optic flow about a set point (Serres et al, 2008a,b). Translational optic flow cues are also used by honeybees (Portelli et al, 2010;Baird et al, 2005;Barron and Srinivasan, 2006;Srinivasan et al, 1996), bumblebees (Baird et al, 2010) and Drosophila (David, 1982;Fry et al, 2009) to control their ground speed.…”
Section: Introductionmentioning
confidence: 99%
“…Flies flew most frequently in central regions of the flight tunnels. This behavior is similar to the centering response in bees (Dyhr and Higgins, 2010;Kirchner and Srinivasan, 1989;Serres et al, 2008;Srinivasan et al, 1991), which is thought to be controlled by the OF in the lateral visual field (Srinivasan et al, 1991). In the straight tunnels, the trajectories covered slightly less than 50% of the tunnel width ( Fig.3B-D).…”
Section: General Flight Characteristicssupporting
confidence: 58%
“…Götz, 1968;Theobald et al, 2010); free flight (Baird et al, 2005;Baird et al, 2006;Baird et al, 2010;David, 1979;David, 1982;Dyhr and Higgins, 2010;Farina et al, 1995;Fry et al, 2009;Frye and Dickinson, 2007;Kern and Varjú, 1998;Preiss, 1993;Serres et al, 2008;Straw et al, 2010)]. It appears that by adjusting their flight speed, insects keep the OF on their eyes at a 'preset' total strength (Srinivasan et al, 1996).…”
Section: Control Of Translational Velocitymentioning
confidence: 99%
“…For visually guided animals in flight, stationary objects in the close environment produce patterns of visual motion on the retina, commonly referred to as optic flow (Gibson, 1994). Numerous studies have shown that optic flow is an important entity in perception that guides motion in space in many flying animals (Bhagavatula et al, 2011;Dyhr and Higgins, 2010;Frye and Dickinson, 2007;Srinivasan, 1996). Optic flow is also important for avoiding collisions or estimating time to contact (Wagner, 1982;Wang and Frost, 1992).…”
Section: Introductionmentioning
confidence: 99%